Growth, morphology and division of flagellates of the genus Trypanoplasma (Protozoa, Kinetoplastida) in vitro - Pecková, H; Lom, J (Parasitology research, 1990)
Nine strains of trypanoplasms were grown in axenic culture. Cultures of Trypanoplasma borreli Laveran and Mesnil, 1901 from fish hosts Blicca bjoerkna, Cyprinus carpio, Scardinius erythrophthalmus and Tinca tinca and of T. guerneyorum Minchin, 1909 from Esox lucius and Trypanoplasma spp. from the leech Piscicola geometra were maintained in biphasic blood-agar medium SNB-9 supplemented with vitamins and antibiotics. In culture, the flagellates transformed into smaller, elongated stages with a little-developed undulating membrane and into short flagella that were morphologically similar to stages in the leech vector. The cultures were passaged weekly at 17-20 degrees C, but they also grew at 4 degrees C. The flagellates divided by binary fission, which was initiated by the formation of two new anterior flagella. The original anterior flagellum of the mother individual was gradually apposed to the cell surface and became the recurrent flagellum of one of the daughter individuals. In the meantime, nuclear division took place, followed by transverse cleavage of the kinetoplast. The division was completed by longitudinal fission of the mother individual into two offspring. Multiple fission that resulted in rosettes, which then cleaved into several daughter cells, was also observed, as well as some dyskinetoplastic and other anomalous forms. In cultures isolated from tenches with high parasitaemia, non-dividing, long filiform stages were observed. Culture stages were not infective for susceptible fishes.
Keywords: Culture Media; Protozoan Infections; Animals; Fish Diseases; Fishes; zvířata; ryby; nemoci ryb; Eukaryota; protozoální infekce; protozoální infekce zvířat; Protozoan Infections, Animal; kultivační média